Barriers to mammography screening in Nigeria: A survey of two communities with different access to screening facilities. (6th January 2019) - Olasehinde, Olalekan; Alatise, Olusegun I.; Arowolo, Olukayode A.; Mango, Victoria L.; Olajide, Olalere S.; Omisore, Adeleye D.; Boutin‐Foster, Carla; Kingham, Thomas P.
Abstract: Delayed presentation of breast cancer is a common theme in most low‐ and middle‐income countries. This study evaluates barriers to mammography screening in two Nigerian communities with different geographic access to screening facilities. A 35 item questionnaire was administered to women, 40 years and older, 1, 169 (52.6%) in Ife Central Local Government where mammography services are offered and 1, 053 (47.4%) in Iwo Local Government where there are no mammography units. Information on breast cancer screening practices and barriers to mammography screening were compared between the two communities. Most women had heard of breast cancer (Ife 94%, Iwo 97%), but few were aware of mammography (Ife 11.8%, Iwo 11.4%). Mammography uptake in Ife Central was 2.8% and 1.8% in Iwo, despite the former offering mammography services. Knowledge and practice of mammography were not statistically different between the two communities ( p = 0.74, 0.1). Lack of awareness was the commonest reason cited for not having mammography in both communities. Others include lack of perceived need and cost. Awareness creation to ensure optimal utilisation of existing facilities, as well as innovative measures to address the barrier of cost, is required to improve breast cancer screening uptake in Nigeria.